Periodontitis and Cardiovasculardisease: Association and Risk (City Dental College Journal, 2018)
Periodontitis has been associated with an increased risk of cardiovascular events.Two internet databases were selected in search of appropriate papers for the study purpose: i)the National Library of Medicine,Washington DC,USA (MEDLINE-PubMed) and ii) HINARI Access to Research in Health Program,World Health Organization,Geneva,Switzerland.Both databases were searched from 1985 to 2009.In the past decades, there has been renewed interest in the old hypothesis that infections increase the risk of developing cardiovascular disease.Atherosclerosis has a major inflammatory component and the main underlying pathological pathway for cardiovascular disease (CVD). Periodontal pathogens may be involved in the initiation and progression of atherosclerosis and subsequent coronary heart disease.Periodontal pathogenPorphyromonasgingivalis caused atherosclerosis in experimental animals and have been found in human atherosclerotic lesions.The nature of association is unclear because both periodontitis and CVD share a host of risk factors.Epidemiological studies, mainly observational studies (case-control,cross-sectional and prospective cohort studies) are usually the first to generate association data between exposure and adverse health outcomes. Clinical trials with statistically significant positive outcomes are easy to interpret and indicate that the tested intervention is effective in favorably altering the adverse health outcomes.Available evidences suggest that having periodontitis contributes to the total infection and inflammation burden and may contribute to cardiovascular events in susceptible subjects.The impact of periodontal therapy must be further investigated. DOI: http://dx.doi.org/10.3329/cdcj.v10i1.13829 City Dent. Coll. J Volume-10, Number-1, January-2013